Secondary Structural Changes in Proteins as a Result of Electroadsorption at Aqueous-Organogel Interfaces - Booth, S.G.; Felisilda, Bren; Alvarez De Eulate, E.; Gustafsson, O.J.R.; Arooj, Mahreen; Mancera, Ricardo; Dryfe, R.A.W.; Hackett, Mark; Booth, S.G.; Arrigan, Damien (AMER CHEMICAL SOC, 2019)
The electroadsorption of proteins at aqueous-organic interfaces offers the possibility to examine protein structural rearrangements upon interaction with lipophilic phases, without modifying the bulk protein or relying on a solid support. The aqueous-organic interface has already provided a simple means of electrochemical protein detection, often involving adsorption and ion complexation; however, little is yet known about the protein structure at these electrified interfaces. This work focuses on the interaction between proteins and an electrified aqueous-organic interface via controlled protein electroadsorption. Four proteins known to be electroactive at such interfaces were studied: lysozyme, myoglobin, cytochrome c, and hemoglobin. Following controlled protein electroadsorption onto the interface, ex situ structural characterization of the proteins by FTIR spectroscopy was undertaken, focusing on secondary structural traits within the amide I band. The structural variations observed included unfolding to form aggregated antiparallel β-sheets, where the rearrangement was specifically dependent on the interaction with the organic phase. This was supported by MALDI ToF MS measurements, which showed the formation of protein-anion complexes for three of these proteins, and molecular dynamic simulations, which modeled the structure of lysozyme at an aqueous-organic interface. On the basis of these findings, the modulation of protein secondary structure by interfacial electrochemistry opens up unique prospects to selectively modify proteins. ©